Analisis Kadar Aspal Optimum Pada Aspal Berpori Menggunakan Aspal PG-76 dan Serat Selulosa - Perdana, Muhammad Gunawan; Pratikso; Mudiyono, Rachmat (Universitas Sarjanawiyata Tamansiswa, 2025)
Porous asphalt is an innovative solution in road pavement to reduce air retention and increase driving safety. This research aims to analyze the optimum asphalt content (KAO) in porous asphalt mixtures using PG-76 asphalt and cellulose fiber materials. PG-76 asphalt was chosen because it has high resistance to permanent cooling, while cellulose fiber is used to increase mix stability and reduce drain-down. The test was carried out using the Marshall method to determine the optimal KAO value based on stability parameters, flow, void content in the mixture, and abrasion resistance using the Cantabro test. The research results show that the use of PG-76 asphalt with the addition of cellulose fiber can improve the mechanical performance of porous asphalt mixtures, especially in increasing resistance to wear and maintaining a high void content. Thus, this mixture has the potential to be applied in road pavement to increase resistance to extreme weather conditions and optimize road drainage functions. The results of this research also provide recommendations for selecting materials and designing porous asphalt mixtures that comply with national and international technical specifications.